Source Code Library (SCL): Application Support Learning Software Development: Source Code Library (SCL): Application Support Learning Software Development - Muhammad Wali; Lukman Ahmad (Jurnal Mantik, 2020)
Learning for software developers enthusiasts both students and faculty has its own problems in learning a programming language. During this practical learning has been widely used by online media. However, problems and obstacles at the time of writing the program code and error code appear an obstacle in developing software for students. This study developed a learning support applications software development so that it becomes a learning solution in software development. In a study using the stages are divided into three tahapyaitu; data collection of pre-development, development and implementation, data collection and post-development, sedangkantahap software development using linear sequential model is often called the waterfall model.